Theorization in sexual education from the grounded theory - Silva, Claudionor Renato da (2019)
Theorization in sexual education is a production of knowledge that, based on inductive researches, such as those using the Grounded Theory (GT) methodology, originate interpretations of reality in specific themes such as gender, child sexuality, adolescent sexuality, teacher training, curriculum, adolescent pregnancy, etc. The purpose of this article is to approach the GT methodology for the production of theorization(s) in the area of sexual education, using an example of a doctoral research in child sexuality that presents the format and characteristics of a theorization with this methodology, aiming, above all, the training of new researchers in the area of sexual education, in undergraduate and postgraduate studies.